Membentuk Kecakapan Partisipatif yang Bermutu: Penerapan Tugas Portofolio Reflektif dalam Perkuliahan Kewarganegaraan di Perguruan Tinggi - Aryaning Arya Kresna; Canggih Gumanky Farunik (Lembaga Yasin AlSys, 2026)
The Civics course in higher education plays a strategic role in developing students’ participatory competencies as citizens, particularly amid the complex social realities of peri-urban areas; however, teaching practices often remain confined to normative approaches that insufficiently accommodate students’ concrete experiences. This study aimed to analyze the influence of using reflective portfolios as an assessment component on the development of students’ participatory competencies in the Civics course at Universitas Pradita during the second semester of the 2024–2025 academic year. The research employed a descriptive qualitative approach with a limited Classroom Action Research design involving 21 students divided into three groups. Data were collected through documentation of students’ reflective portfolios and structured interviews, then analyzed through processes of data reduction, categorization, and interpretation based on the framework of civic knowledge, civic skills, and civic disposition. The findings show that reflective portfolios are effective in strengthening students’ conceptual understanding of citizenship issues, developing participatory skills and public communication, and fostering empathy and participatory awareness as citizens. The study concludes that reflective portfolios function not only as assessment instruments but also as transformative learning media that are relevant to students’ social context, thereby underscoring the importance of integrating reflective assessment into Civics learning to support character education and the formation of active and responsible citizens.